PECULIARITIES OF SYNOVIOCYTES AND CHONDROCYTES PROLIFERATIVE ACTIVITY IN RATS WITH EXPERIMENTAL MODEL OF UNDIFFERENTIATED DYSPLASIA OF CONNECTIVE TISSUE - Hryhorieva, O.A.; Pivtorak, V.I.; Popovych, Yu.I.; Abrosimov, Yu.Yu.; Tavrog, M.L. (World of Medicine and Biology, 2021)
The purpose of the work was to study the dynamics of proliferative activity of the synovial membrane cells of the joint capsule and articular cartilage chondrocytes of rats in the postnatal period on the background of experimental model of undifferentiated dysplasia of connective tissue. It was formed in Wistar rats by means of subcutaneous injection with human immunoglobulin on the 18th day of fetal period of development according to the method elaborated by N. A.Voloshyn (1981). It was revealed, that during the first two weeks after birth in experimental rats proliferative activity of synovial membrane cells is significantly decreased in comparison with control. The distribution of ki-67+ cells in different zones of the articular cartilage of the distal epiphysis of rats’ femur during the first month of life is different depending on the degree of morphological and functional differentiation of chondrocytes. In rats with experimental undifferentiated dysplasia of connective tissue the increased proliferative activity of articular cartilage chondrocytes in all morphofunctional zones reduces at the 11th, 14th days after birth, this is associated with earlier formation of subchondral bone (at the 11th day compared to the 14th in control group) and the change in the rate of differentiation and functional activity of chondrocytes.